2008
DOI: 10.1371/journal.pone.0002016
|View full text |Cite
|
Sign up to set email alerts
|

A Test of Highly Optimized Tolerance Reveals Fragile Cell-Cycle Mechanisms Are Molecular Targets in Clinical Cancer Trials

Abstract: Robustness, a long-recognized property of living systems, allows function in the face of uncertainty while fragility, i.e., extreme sensitivity, can potentially lead to catastrophic failure following seemingly innocuous perturbations. Carlson and Doyle hypothesized that highly-evolved networks, e.g., those involved in cell-cycle regulation, can be resistant to some perturbations while highly sensitive to others. The “robust yet fragile” duality of networks has been termed Highly Optimized Tolerance (HOT) and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 81 publications
(89 reference statements)
0
26
0
1
Order By: Relevance
“…Each pathway is subject to an intensive study by the computational systems biology approach: modelling of the cell cycle [65][66][67][68][69][70][71][72][73], apoptosis [74][75][76], MAPK and PI3K/AKT pathways [77,78]. As these pathways are involved in cell proliferation, survival and cell death, computational models of these pathways are considered promising tools in cancer research for prediction of cancer disease progression, development of biomarkers, and drug therapy efficacy [79][80][81][82]. Henceforth, understanding the complex regulation of B-CLL disease pathogenesis, requires a strategic knowledge on the models of the cell cycle, and apoptosis that report on intrinsic and extrinsic cell signaling network.…”
Section: Systems Biology Approachmentioning
confidence: 99%
See 4 more Smart Citations
“…Each pathway is subject to an intensive study by the computational systems biology approach: modelling of the cell cycle [65][66][67][68][69][70][71][72][73], apoptosis [74][75][76], MAPK and PI3K/AKT pathways [77,78]. As these pathways are involved in cell proliferation, survival and cell death, computational models of these pathways are considered promising tools in cancer research for prediction of cancer disease progression, development of biomarkers, and drug therapy efficacy [79][80][81][82]. Henceforth, understanding the complex regulation of B-CLL disease pathogenesis, requires a strategic knowledge on the models of the cell cycle, and apoptosis that report on intrinsic and extrinsic cell signaling network.…”
Section: Systems Biology Approachmentioning
confidence: 99%
“…Cell cycle modelling demonstrated that despite extensive control mechanisms in regulating phase transitions, it can lose its control and become a fragile system when variations in specific parameters of the model that affect robustness are introduced. From a clinical point of view, this fragility in the system can be referred to as cell cycle malfunction, observed as uncontrolled cell proliferation, a common phenomenon underlying many cancers [82].…”
Section: Systems Biology Approachmentioning
confidence: 99%
See 3 more Smart Citations